Squamous Papilloma of the External Auditory Canal as a High-Fidelity Mimic of Malignant Otitis Externa: A Case Report - I Gusti Ayu Mahaprani Danastri; Ketut Tadeus Max Nurcahya Pinatih; Made Lely Rahayu (Archives of The Medicine and Case Reports, 2025)
Malignant otitis externa (MOE) is a life-threatening osteomyelitis of the skull base, typically affecting geriatric patients with diabetes mellitus. Its initial presentation of otalgia, otorrhea, and an external auditory canal (EAC) mass demands an immediate, high index of suspicion. Squamous papilloma, a benign human papillomavirus (HPV)-related neoplasm, is exceedingly rare in the EAC. This report details a case where this rare benign entity presented as a high-fidelity clinical and laboratory mimic of MOE. We present the case of a 71-year-old female with poorly controlled Type 2 Diabetes Mellitus who presented with a three-week history of severe, refractory otalgia. A systematic diagnostic evaluation was performed, including clinical examination, full audiological assessment, serum inflammatory markers, and high-resolution computed tomography (HRCT) of the temporal bones. The patient's presentation was a textbook surrogate for MOE, including severe otalgia, purulent otorrhea, a friable EAC mass, and markedly elevated erythrocyte sedimentation rate (ESR) (78 mm/hr) and C-Reactive Protein (CRP) (45.2 mg/L). However, HRCT demonstrated an occluding soft-tissue mass without the hallmark finding of temporal bone erosion. The patient underwent transcanal excisional biopsy. Histopathological (H&E) analysis provided the definitive diagnosis of a benign squamous papilloma, with pathognomonic koilocytosis consistent with HPV infection. The patient's severe symptoms resolved completely upon excision. In conclusion, this case highlights a critical diagnostic pitfall. A secondarily infected EAC squamous papilloma can create a clinical and laboratory picture indistinguishable from early-stage MOE. The absence of bony erosion on HRCT is the single most critical finding to pivot the diagnosis away from invasive osteomyelitis. This report underscores the mandatory role of a systematic diagnostic pathway combining imaging and histopathology to prevent misdiagnosis and avoid unnecessary, prolonged, and toxic systemic antimicrobial therapy.